2020
DOI: 10.1007/s10608-020-10143-y
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Covid-19 Experiences and Associated Stress on Anxiety, Depression, and Functional Impairment in American Adults

Abstract: Background The COVID-19 pandemic has had a profound impact on health and well-being worldwide and there is increasing recognition of the need to understand the psychological impact of COVID-19 experiences and stress in addition to the physical health consequences. Methods The present study examined how experiences related to COVID-19 and associated stress impact, anxiety, depression, and functional impairment in a convenience sample of 565 American adults (57.9% male) recruited through MTURK. Results COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
173
6
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 222 publications
(230 citation statements)
references
References 44 publications
20
173
6
2
Order By: Relevance
“…Among the ones who presented with previous diagnosis of depression, these effects were more intense 32 . Such results are in accordance with findings from international studies, which assessed the mental health of individuals during the pandemic [32][33][34][35][36] .…”
Section: Discussionsupporting
confidence: 91%
“…Among the ones who presented with previous diagnosis of depression, these effects were more intense 32 . Such results are in accordance with findings from international studies, which assessed the mental health of individuals during the pandemic [32][33][34][35][36] .…”
Section: Discussionsupporting
confidence: 91%
“…The results of this survey show that the anxiety score of rural residents in Hunan during the COVID-19 epidemic was higher than that of healthy Chinese (26) and rural residents across China (27) during the non-epidemic period. Our research found that the detection rate of anxiety among rural residents in Hunan was 17.88%, while one Turkish study reported that the detection rate of anxiety in people was 45.1% (28) while a study on American adults found a rate of 38.41% (29). The reason for this difference may be that our research was carried out in February, while their research was mainly carried out in April 2020.…”
Section: Discussion Anxiety Status Of Rural Residents In Hunan Duringcontrasting
confidence: 57%
“…Racial/Ethnic minorities are at an elevated risk for severe outcomes due to COVID-19 and healthcare workers and parents with children at home have been experiencing novel stressors during the pandemic. Not surprisingly, research has demonstrated that symptoms of anxiety and depression are elevated overall, but are not universal across individuals (e.g., Barzilay et al, 2020;Gallagher, Zvolensky, et al, 2020;Xiong et al, 2020). There is increasing evidence regarding psychological factors that may confer risk to elevated distress during the pandemic, but limited research on sources of psychological resilience that may promote greater wellbeing or allow individuals to flourish even during stressful events such as the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%